(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
This research applies the visual analysis software Citespace to conduct a statistical and comparative analysis of Chinese language teaching (CLT) until this moment in Spanish-speaking countries by using two databases: China National Knowledge Infrastructure (CNKI) and Dialnet from Spain. This analysis focuses on the publication year, authorship, co-authorship, keyword clustering, and other relevant article indicators, etc. It aims to summarize the differences and similarities in CLT in Spanish-speaking countries between China and Spanish-speaking countries nowadays. The research reveals that academic studies on CLT in Spanish-speaking countries are quite similar between China and Spain. Research in both China and Spain regarding CLT in Spanish-speaking countries is increasing and has underlaid fruitful results. However, differences have been found in the depth, breadth, and interdisciplinary perspectives of such research. Through the analysis of CLT in both regions, this study concludes that both need to strengthen and integrate cooperation and exchange in the academic field of CLT to leverage their respective strengths and learn from each other.